2019
DOI: 10.1093/cid/ciz696
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Direct-acting Antivirals for Chronic Hepatitis C Virus Infection in People Who Inject Drugs or Receive Opioid Substitution Therapy: A Systematic Review and Meta-analysis

Abstract: Background Treatment uptake for hepatitis C virus (HCV) infection in people who inject drugs (PWID) and patients on opioid substitution therapy (OST) is still low despite treatment guidelines that advocate the use of direct-acting antivirals (DAAs) in all patients. Our aim in this review was to investigate treatment outcomes among PWID and patients on OST in comparison to control cohorts. Methods A search of Embase, Medline, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
43
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(51 citation statements)
references
References 36 publications
6
43
1
1
Order By: Relevance
“…The included PWIDs showed excellent adherence to therapy with only a very limited number of scheduled DAA-ingestions being missed and, most importantly, an SVR rate of 98.6%-which was in fact similar to the SVR rate of 98.6% achieved in patients with presumed "excellent compliance" with G/P self-administration. The observed excellent safety profile of G/P as well as the high SVR rates that did not relevantly deviate from the treatment outcomes in patients without a history of IDU go in line with literature and support the recommendations of broad access to HCV treatment [35,36].…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The included PWIDs showed excellent adherence to therapy with only a very limited number of scheduled DAA-ingestions being missed and, most importantly, an SVR rate of 98.6%-which was in fact similar to the SVR rate of 98.6% achieved in patients with presumed "excellent compliance" with G/P self-administration. The observed excellent safety profile of G/P as well as the high SVR rates that did not relevantly deviate from the treatment outcomes in patients without a history of IDU go in line with literature and support the recommendations of broad access to HCV treatment [35,36].…”
Section: Discussionsupporting
confidence: 85%
“…Various studies have shown that DAA therapy for HCV is safe in PWIDs, even in the presence of ongoing IDU and/or OST, and leads to excellent cure rates that do not deviate much from patients without a history of IDU [35,36]. We hypothesized that directly observed DAA therapy along with OST under the supervision of medical staff at local pharmacies or lowthreshold facilities would further increase DAA adherence and improve HCV treatment outcomes in PWIDs on stable OST with or without ongoing IDU.…”
Section: Discussionmentioning
confidence: 99%
“…Our results are consistent with previous reports from other countries. 21,22 A systematic review reported a 5-year HCV recurrence rate of 10.67%, driven mainly by reinfection in IDUs or prisoners. 7 To eliminate HCV in PWID, long-term follow-up after DAA therapy is necessary.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the discontinuation rate in recent PWID was extremely low (2%). In fact, other groups have confirmed low discontinuation rates in PWID that were not different to non‐PWID populations with DAA treatment …”
mentioning
confidence: 92%